2020
DOI: 10.1136/gpsych-2019-100117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine in electroconvulsive therapy for major depressive disorder: meta-analysis of randomised controlled trials

Abstract: BackgroundThe use of ketamine in electroconvulsive therapy (ECT) has been examined in the treatment of major depressive disorder (MDD); however, there has been no systematic review and meta-analysis of related randomised controlled trials (RCTs).AimTo examine the efficacy and safety of ketamine augmentation of ECT in MDD treatment.MethodsTwo reviewers searched Chinese (China National Knowledge Infrastructure and Wanfang) and English (PubMed, PsycINFO, Embase and Cochrane Library) databases from their inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(47 reference statements)
0
4
0
1
Order By: Relevance
“…One previous study performed a pairwise meta-analysis on ketamine versus propofol versus ketamine plus propofol using three RCTs, 60 and concluded that ketamine alone and the combination of ketamine and propofol had greater efficacy in the treatment of depressive symptoms. However, this study only considered a single ECT session and excluded studies with two or more ECT sessions.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study performed a pairwise meta-analysis on ketamine versus propofol versus ketamine plus propofol using three RCTs, 60 and concluded that ketamine alone and the combination of ketamine and propofol had greater efficacy in the treatment of depressive symptoms. However, this study only considered a single ECT session and excluded studies with two or more ECT sessions.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found on any outcome measure during, at the end of or 1 month following the ECT course. Li XM et al [8] examined the efficacy and safety of ketamine augmentation of ECT in MDD treatment. Four RCTs (n = 239) compared ketamine alone or ketamine plus propofol (n = 149) versus propofol alone (n = 90) in patients with MDD who underwent a single ECT session.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, no added benefit in the depression scores has been observed at the end of the index course ECT performed under ketamine anesthesia [109][110][111]. On the other hand, ketamine has been shown to provide better seizure quality regardless of the administered dose, compared with nonketamine anesthesia [111].…”
Section: Ketamine and Electroconvulsive Therapymentioning
confidence: 98%